2003
DOI: 10.1002/ajmg.a.20527
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic congenital central hypoventilation syndrome: Analysis of genes pertinent to early autonomic nervous system embryologic development and identification of mutations in PHOX2b

Abstract: Idiopathic congenital central hypoventilation syndrome (CCHS) has been linked to autonomic nervous system dysregulation and/or dysfunction (ANSD) since it was first described in 1970. A genetic basis of CCHS has been proposed because of the reports of four families with two affected children, because of mother-child transmission, and because of a recent report of a polyalanine expansion mutation in PHOX2b in a subset of CCHS subjects. We, therefore, studied genes pertinent to early embryologic development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
185
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 348 publications
(193 citation statements)
references
References 69 publications
(84 reference statements)
6
185
1
1
Order By: Relevance
“…Third, these results reiterate the need to carefully consider the mechanism chosen for PHOX2B testing among probands and among parents of probands in order to optimize management, assure safety and physiologic stability, and to determine risk of recurrence in subsequent offspring. This report supports previous findings [3][4][5] indicating inheritance of PHOX2B mutations from parental carriers with very low levels of somatic mosaicism (as low as 5% here). Although sequencing of the PHOX2B gene has become the most commonly available form of clinical testing in CCHS families, studies have shown it to be inadequate to identify low-level mosaicism.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Third, these results reiterate the need to carefully consider the mechanism chosen for PHOX2B testing among probands and among parents of probands in order to optimize management, assure safety and physiologic stability, and to determine risk of recurrence in subsequent offspring. This report supports previous findings [3][4][5] indicating inheritance of PHOX2B mutations from parental carriers with very low levels of somatic mosaicism (as low as 5% here). Although sequencing of the PHOX2B gene has become the most commonly available form of clinical testing in CCHS families, studies have shown it to be inadequate to identify low-level mosaicism.…”
supporting
confidence: 93%
“…Specifically, they have confirmed the autosomal dominant inheritance pattern 2,3 and described the incidence of somatic mosaicism or full mutation in parents of CCHS probands in the Japanese cohort (22%)-reflecting similar figures to the report (using the same methodology) as Bachetti et al 4 These results raise several important points in regard to genetic and physiologic testing procedures in CCHS families. First, the results emphasize the importance of genetic counseling for families in which a CCHScausing PHOX2B mutation is identified.…”
supporting
confidence: 77%
“…A genetic background for isolated cases of CCHS has been established through findings of variants such as expansions of the polyalanine tract of exon 3 of the PHOX2b gene in up to 97% of patients Weese-Mayer et al, 2003;Gaultier et al, 2004;Berry-Kravis et al, 2006). Such variants, however, cannot account for the concomitant presentation of Hirschsprung's disease in up to 20% of CCHS patients, which suggests that other genes may be involved in the combined CCHS/HSCR phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The main genetic variants detected in CCHS patients have been mutations (deletions or expansions) in the PHOX2b gene, which in some series are present in up to 97% of isolated cases (Weese-Mayer et al, 2003). Most of these variants occur within the polyalanine tract in exon 3 Gaultier et al, 2004), yet 14 non-polyalanine repeat-expansion mutations have also been found in 184 CCHS patients and were linked to a more severe phenotype, with increased prevalence of continuous ventilatory dependence, Hirschsprung disease (HSCR) and neural crest tumours (Berry-Kravis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…About 90% of patients have de novo polyalanine expansion mutations in the polyalanine tract of 20 residues. [1][2][3][4][5][6] Approximately 5% of patients inherit polyalanine expansion mutations mostly from asymptomatic parents with somatic mosaicism and rarely from affected parents. Polyalanine expansion disorders constitute one family of homopolymer expansion disorders, including at least nine disorders.…”
Section: Congenital Central Hypoventilation Syndrome (Cchs; Mim 209880)mentioning
confidence: 99%